Amyloid-PET burden and regional distribution in cerebral amyloid angiopathy: a systematic review and meta-analysis of biomarker performance. Issue 4 (25th October 2017) - Charidimou, Andreas; Farid, Karim; Tsai, Hsin-Hsi; Tsai, Li-Kai; Yen, Rouh-Fang; Baron, Jean-Claude
Abstract : Introduction: We performed a meta-analysis to synthesise current evidence on amyloid-positron emission tomography (PET) burden and presumed preferential occipital distribution in sporadic cerebral amyloid angiopathy (CAA). Methods: In a PubMed systematic search, we identified case–control studies with extractable data on global and occipital-to-global amyloid-PET uptake in symptomatic patients with CAA (per Boston criteria) versus control groups (healthy participants or patients with non-CAA deep intracerebral haemorrhage) and patients with Alzheimer's disease. To circumvent PET studies' methodological variation, we generated and used 'fold change', that is, ratio of mean amyloid uptake (global and occipital-to-global) of CAA relative to comparison groups. Amyloid-PET uptake biomarker performance was then quantified by random-effects meta-analysis on the ratios of the means. A ratio >1 indicates that amyloid-PET uptake (global or occipital/global) is higher in CAA than comparison groups, and a ratio <1 indicates the reverse. Results: Seven studies, including 106 patients with CAA (>90% with probable CAA) and 138 controls (96 healthy elderly, 42 deep intracerebral haemorrhage controls) and 72 patients with Alzheimer's disease, were included. Global amyloid-PET ratio between patients with CAA and controls was above 1, with an average effect size of 1.18 (95% CI 1.08 to 1.28; p<0.0001). Occipital-to-global amyloid-PET uptake ratio did not differ between patients with CAA versus patients with deep intracerebral haemorrhage or healthy controls. By contrast, occipital-to-global amyloid-PET uptake ratio was above 1 in patients with CAA versus those with Alzheimer's disease, with an average ratio of 1.10 (95% CI 1.03 to 1.19; p=0.009) and high statistical heterogeneity. Conclusions: Our analysis provides exploratory actionable data on the overall effect sizes and strength of amyloid-PET burden and distribution in patients with CAA, useful for future larger studies.